Assessment of levels of Heavy Metals in Mechanic Village Dumpsite (along Imiringe Road) in Yenagoa - Ukpe, Richard A.; Johnson, Ekarika C. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Distribution of Cr, Cd, Pb, Sb, V and Ni ions in soils within the Yenagao mechanic workshop dumpsite was studied by analyzing the soil samples for their heavy metal ion concentration using atomic absorption spectrophotometer. The results indicated that soil concentrations of the studied heavy metal ions to be below the permissible limit. However, point of concern was raised considering the relative closeness of most of the metal ion concentrations to the limits, which indicated future contamination risk. Lead ion was the most concentrated heavy metal ion.